Analysis of Service Quality in m-Health - Annisa Nuria Rodhiani, Rahmat Nurcahyo, Muhammad Dachyar (International Journal of Advanced Science and Technology, 2020)
The rapid development of technology has impacted on several fields including digital revolution of health sector. In Indonesia, the journey to ease is becoming more open, now that distance treatment is increasingly possible, people are starting to use their electronic devices to consult with doctors, order and buy medicines, and even to collect patient health data. Although mobile health creates positive change, concerns about quality have an impact on users’ satisfaction, continuing intentions, and quality of life. Thus, the impact of perceived quality of this service becomes an important dimension in determining the success or failure of the mobile health platform. The main purpose of this study is to determine attribute that affect customer satisfaction using Kano model and SERVQUAL which better defines customer expectations and measures the effects of these attributes in determining the success or failure of mobile health platform.